2021
DOI: 10.1021/acsami.0c18930
|View full text |Cite
|
Sign up to set email alerts
|

Light-Activated Antimicrobial Surfaces Using Industrial Varnish Formulations to Mitigate the Incidence of Nosocomial Infections

Abstract: Evidence has shown that hospital surfaces are one of the major vehicles of nosocomial infections caused by drug-resistant pathogens. Smart surface coatings presenting multiple antimicrobial activity mechanisms have emerged as an advanced approach to safely prevent this type of infection. In this work, industrial waterborne polyurethane varnish formulations containing for the first time cationic polymeric biocides (SPBs) combined with photosensitizer curcumin were developed to afford contact-active and light-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…As an illustration, Müller et al reported polyethersulfone membranes doped with polycationic PS that provide antimicrobial properties for potential use as filter membranes in water purification or medicine [340]. Other recent distinctive systems for aPDI refer to self-sterilizing and photoactive antimicrobial surfaces made from (i) natural polymers such as chitosan doped with chlorophyll [336], (ii) "bioplastic" poly(lactic acid) surfaces coated with a BODIPY PS [341], or (iii) synthetic polyurethanes doped with curcumin and cationic bacterial biocides [336,[342][343][344][345].…”
Section: Polymeric Nps and Nanocompositesmentioning
confidence: 99%
“…As an illustration, Müller et al reported polyethersulfone membranes doped with polycationic PS that provide antimicrobial properties for potential use as filter membranes in water purification or medicine [340]. Other recent distinctive systems for aPDI refer to self-sterilizing and photoactive antimicrobial surfaces made from (i) natural polymers such as chitosan doped with chlorophyll [336], (ii) "bioplastic" poly(lactic acid) surfaces coated with a BODIPY PS [341], or (iii) synthetic polyurethanes doped with curcumin and cationic bacterial biocides [336,[342][343][344][345].…”
Section: Polymeric Nps and Nanocompositesmentioning
confidence: 99%
“…Although the FRP technique is one of the main methods for obtaining QA-based polymers in terms of scaling up the process, controlled radical polymerization (CPR) methods allow precise control of the molecular weight and macromolecular structure of the resulting polymer, which is important for obtaining better antibacterial activity. CRP techniques, such as atom transfer radical polymerization (ATRP), reversible addition–fragmentation chain transfer (RAFT), ,, and nitroxide-mediated polymerization (NMP) are being actively studied to create QA-antibacterial coatings. In addition, the literature describes examples of obtaining QA-functionalized surfaces/materials using ring-opening polymerization and click chemistry methods. , …”
Section: Qac-embedded Coatings As a Promising Strategy For Biofilm Co...mentioning
confidence: 99%
“…because of i) its lower cost and environmental friendliness, which greatly increases the potential for large-scale applications; ii) its lower film-forming temperature (as low as 0 °C), which broadens the environmental applicability without high temperature curing; iii) its higher weather resistance, which would be beneficial to improve outdoor application ability. [40][41][42][43] Ethanol was selected as a solvent because of its environmental friendliness and high volatility to ensure rapid evaporation after spraying on the substrate. The schematic illustration of the fabrication of superhydrophobic coatings was shown in Figure 1a.…”
Section: Fabrication Wettability and Surface Morphology Of Coatingsmentioning
confidence: 99%